APPLICATION OF THE METHOD «FMEA» IN FOOD SAFETY MANAGEMENT SYSTEMS (Academia Science Repository, 2023)
At food industry enterprises, it is important to prevent or reduce risks in the production process, to prevent their recurrence. In this regard, the analysis method FMEA (Potential Failure Mode and Effects Analysis) provides the necessary results in the analysis of the root causes of each possible or occurring defect and taking measures to prevent recurrence. This article presents an analysis of FMEA in the implementation of management systems in food industry enterprises, the practice of its application.